2013
DOI: 10.1073/pnas.1220895110
|View full text |Cite
|
Sign up to set email alerts
|

RAC1 P29S is a spontaneously activating cancer-associated GTPase

Abstract: RAC1 is a small, Ras-related GTPase that was recently reported to harbor a recurrent UV-induced signature mutation in melanoma, resulting in substitution of P29 to serine (RAC1 P29S ), ranking this the third most frequently occurring gain-of-function mutation in melanoma. Although the Ras family GTPases are mutated in about 30% of all cancers, mutations in the Rho family GTPases have rarely been observed. In this study, we demonstrate that unlike oncogenic Ras proteins, which are primarily activated by mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
151
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(164 citation statements)
references
References 42 publications
5
151
0
Order By: Relevance
“…Notably, Rac1 activity levels were very low in the wild-type Rac1 melanoma lines, A375 and 31T (data not shown). These results suggest that the zygosity of RAC1-P29S correlates with RAC1 activation in the cells, strengthening the claim that the mutant encodes for an active RAC1, as previously shown [57]. …”
supporting
confidence: 86%
See 1 more Smart Citation
“…Notably, Rac1 activity levels were very low in the wild-type Rac1 melanoma lines, A375 and 31T (data not shown). These results suggest that the zygosity of RAC1-P29S correlates with RAC1 activation in the cells, strengthening the claim that the mutant encodes for an active RAC1, as previously shown [57]. …”
supporting
confidence: 86%
“…RAC1-P29S was shown to bind more GTP, as well as downstream effectors such as PAK1 and MLK3 [53,54]. It also induces ERK phosphorylation, cell proliferation, membrane ruffling, and transwell migration in normal cells [54,57]. The general mode of action of Rac1, and its P29S mutant, are shown in Fig.…”
Section: Europe Pmc Funders Groupmentioning
confidence: 98%
“…We propose that the GEF domain in PREX2 truncating mutants is activated because of the removal of the autoinhibitory C terminus, as shown for other GEFs including the highly similar PREX1 (24,25,46). Interestingly, Rac1 is recurrently mutated and constitutively activated in cutaneous melanoma (47,48). Hence, overactivation of Rac1 signaling pathway either through direct mutational activation or through its upstream regulators (e.g., PREX2) appears to be an emerging theme in melanoma biology.…”
Section: Discussionmentioning
confidence: 73%
“…Rac1 is also important in various oncogenesis pathways including initiation, progression, invasion and metastasis (Davis et al 2013) and stress sensing (Han et al 2001). The Insert region is essential for mitogenesis and apoptosis.…”
Section: Alterations In Lipid Membranesmentioning
confidence: 99%
“…Rac1 GEFs have recently been reported to have important roles in cancer (Wertheimer et al 2012;Davis et al 2013). It has been shown that Trp56, which is present between the two switch regions, is the necessary and critical amino acid of Rac1; hence targeting the Trp56 site by an interfering compound can affect the Rac1 activity (Gao et al 2001).…”
Section: Alterations In Lipid Membranesmentioning
confidence: 99%